Orian Five Printing Enterprise/ Ahmad Sabri Kamarozaman... [et al.] - Kamarozaman, Ahmad Sabri; Ibrahim, Mohd Hilmi; Abu Seman, Sahrul Azwan; Mohd Ramli, Zaleha; Mohamad, Noor Jehan (2001)
Orian Five Enterprise is set up with its general objective, which is to provide excellent service and product in printing industry. This business allow customers to earn quality service and product. Their business is located at Sungai Dua, Penang. They provide printing service that are basically based on paper. Customer can obtain any kind of printed product from their company. They also receive orders for printing items like business card, books, magazines, pamphlet, wedding card, calendar and poster. However, they also accept orders for items beside what they normally print. The business was started on 1st January 2004.